The influence of tax, tunneling incentive, and bonus mechanisms on transfer pricing decision in manufacturing companies - Yasfiana Nuril Indriaswari; Riski Aprillia Nita (Universitas Hayam Wuruk Perbanas, 2017)
Transfer pricing is a way conducted by a multinational company to do tax avoidance. Concentrated ownership structure makes the majority shareholders tend to perform a tunneling incentive that could harm minority shareholders. Companies that set bonus mechanism based on the profits will make the management or the board of directors tend to conduct profit manipulation. The aim of this research is to analyze the influence of tax, tunneling incentive and bonus mechanism on transfer pricing decision taken by manufacturing companies listed on the Indonesia Stock Exchange. The sample used on this study is manufacturing companies listed on the Indonesia Stock Exchange in 2012-2014 totaling 69 companies taken using purposive sampling method. The analysis technique used in this study is analysis binary logistic regression. The result of this study shows that tax and tunneling incentive have significantly influence on transfer pricing, while bonus mechanism does not have significant influence on transfer pricing